Pengaruh Aktivitas Organisasi dan Intensitas Belajar Mahasiswa Pendidikan Matematika Terhadap Prestasi Belajar - Ari Suningsih; Imam Nurohim; Windi Ria Astuti (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
The study aimed to determine the effect of participating in the exact student association organization (HIMEKS) and the intensity of learning on student achievement in mathematics education at FKIP-UMPRI. The activity in question was the involvement and an essential role in the organization's activities to foster and develop talents and increase student motivation. The intensity of learning included motivation, time or duration, discipline, concentration, frequency, activity, and presentation. This type of research used ex post facto with a quantitative approach. The population was all students of mathematics education FKIP-UMPRI. The research sample was Himeks administrators who were taken using a purposive sampling technique, totaling 43 people. Data collection through the distribution of questionnaires and documentation. The data analysis technique used simple regression analysis technique and multiple regression analysis. The results of data analysis: (1) there was an effect of activities following the HIMEKS organization with a contribution of 9.1% on student learning achievement. A positive effect with a correlation coefficient (r_x1y) of 0.302 with a low category; (2) there was an effect of learning intensity on student achievement with a contribution of 28.7%. The positive effect showed by the correlation coefficient (r_x2y) of 0.536, including the medium category; (3) there was an effect of participating in the HIMEKS organization and the intensity of learning together on student learning achievement 32.0%. A positive effect with a correlation coefficient of r_x1x2y=0.566 in the medium category.